Microglial Nox2 Plays a Key Role in the Pathogenesis of Experimental Autoimmune Encephalomyelitis - Hu, Chih-Fen; Wu, San-Pin; Lin, Gu-Jiun; Shieh, Chi-Chang; Hsu, Chih-Sin; Chen, Jing-Wun; Chen, Shih-Heng; Hong, Jau-Shyong; Chen, Shyi-Jou (Frontiers in Immunology, 2021)
While oxidative stress has been linked to multiple sclerosis (MS), the role of superoxide-producing phagocyte NADPH oxidase (Nox2) in central nervous system (CNS) pathogenesis remains unclear. This study investigates the impact of Nox2 gene ablation on pro- and anti-inflammatory cytokine and chemokine production in a mouse experimental autoimmune encephalomyelitis (EAE) model. Nox2 deficiency attenuates EAE-induced neural damage and reduces disease severity, pathogenic immune cells infiltration, demyelination, and oxidative stress in the CNS. The number of autoreactive T cells, myeloid cells, and activated microglia, as well as the production of cytokines and chemokines, including GM-CSF, IFN, TNF, IL-6, IL-10, IL-17A, CCL2, CCL5, and CXCL10, were much lower in the Nox2-/- CNS tissues but remained unaltered in the peripheral lymphoid organs. RNA-seq profiling of microglial transcriptome identified a panel of Nox2 dependent proinflammatory genes: Pf4, Tnfrsf9, Tnfsf12, Tnfsf13, Ccl7, Cxcl3, and Cxcl9. Furthermore, gene ontology and pathway enrichment analyses revealed that microglial Nox2 plays a regulatory role in multiple pathways known to be important for MS/EAE pathogenesis, including STAT3, glutathione, leukotriene biosynthesis, IL-8, HMGB1, NRF2, systemic lupus erythematosus in B cells, and T cell exhaustion signaling. Taken together, our results provide new insights into the critical functions performed by microglial Nox2 during the EAE pathogenesis, suggesting that Nox2 inhibition may represent an important therapeutic target for MS.